Aristotle's Topics - Slomkowski, Paul. (Philosophia Antiqua, 1997)
This work deals with Aristotle's Topics , a textbook on how to argue successfully in a debate organised in a certain way. The origins of the three branches of logic can be found here: logic of propositions, of predicates and of relations. Having dealt with the structure of the dialectical debates and the theory of the predicables, the central notion of the topos is analysed. Topoi are principles of arguments designed to help a disputant refute his opponent and function as hypotheses in hypothetical syllogisms, the main form of argument in the Topics . Traces of the crystallization of their theory can be found in the Topics and Analytics . The author analyses a selection of topoi including those according to which categorical and relational syllogisms are constructed.